2012
DOI: 10.1093/eurheartj/ehs042
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the importance of CYP2C19 and PON1 in the mechanism of clopidogrel bioactivation and in vivo antiplatelet response

Abstract: Our results demonstrate that PON1 does not mediate clopidogrel active metabolite formation or antiplatelet action, while CYP2C19 activity and genotype remains a predictor of clopidogrel pharmacokinetics and antiplatelet response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 33 publications
5
61
0
2
Order By: Relevance
“…In contrast, in our study, the formation of H4 from thiolactone 2 by CYP2C8 was negligible (data not shown). Gong et al (2012) reported that CYP2C19 and CYP3A4 were involved in the formation of H4 from thiolactone 2, which was consistent with our study. CYP2B6 and CYP3A4 are subjected to induction and inhibition, which may affect the metabolism and efficacy of clopidogrel.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, in our study, the formation of H4 from thiolactone 2 by CYP2C8 was negligible (data not shown). Gong et al (2012) reported that CYP2C19 and CYP3A4 were involved in the formation of H4 from thiolactone 2, which was consistent with our study. CYP2B6 and CYP3A4 are subjected to induction and inhibition, which may affect the metabolism and efficacy of clopidogrel.…”
Section: Discussionsupporting
confidence: 93%
“…This was followed by a series of additional healthy volunteer studies that confirmed the impact of CYP2C19 genotype on the antiplatelet effect and provided evidence for loss of function variant carriers having significantly lower plasma concentrations of the clopidogrel active metabolite (Brandt et al, 2007;Kim et al, 2008;Umemura et al, 2008). Cardiovascular Pharmacogenetics and Personalized Medicine Numerous studies in patients with cardiovascular disease further documented that CYP2C19 loss of function carriers have reduced concentrations of active metabolite and less antiplatelet effect (Mega et al, 2009;Varenhorst et al, 2009;Collet et al, 2011;Hulot et al, 2011;Gong et al, 2012;Price et al, 2012). As a result, there is little to no discrepancy in the literature regarding the impact of the CYP2C19 loss of function alleles on clopidogrel active metabolite concentrations or on-treatment platelet reactivity.…”
Section: B Cyp2c19 Genetic Polymorphismsmentioning
confidence: 92%
“…At last, ] i ) was determined as described previously. [27][28][29][30][31] Briefly, washed platelets were resuspended at concentrations of 10 8 /mL in modified Tyrode buffer (136.5 mM NaCl, 2.68 mM KCl, 11.9 mM NaHCO 3 , 0.42 mM NaH 2 PO 4 , 1 mM MgCl 2 , 5 mM N-(2-hydroxyethyl) piperazine-N′-2-ethanesulfonic acid (Hepes), 1.11 mM dextrose, 0.35% BSA, pH 7.4) with 10 U/mL heparin, 0.2 U/mL Apyrase and 1 µM prostaglandin I 2 (PGI 2 ), and then incubated for 8 min. After centrifugation, about 10 8 platelets were incubated in 300 µL of modified Tyrode buffer with 2.5 mM probenecid, 0.02% pluronic, 10 µM Fluo-3, 0.5 µM PGI 2 and 0.02 U/mL apyrase for 40 min at 37°C and washed, while the test drug was added in the last 10 min.…”
Section: Methodsmentioning
confidence: 99%